Travel records (游记 youji) for gardens as source for researching officials’ private lives in 11th-century China - Stepanova, Jekaterina (Acta Orientalia Vilnensia, 2007)
This article deals with the 11th century travel records (youji) for the gardens in Luoyang. These texts were usually ordered by owners of gardens and were written by famous authors. According to youji materials, a Chinese garden can be presented as a part of nature, a source of pleasure, or a shelter for a hermit, so the article is divided into these three parts. Through the descriptions of gardens in youji, not only the craft of gardening, but also the way of life and private life of garden owners can be examined.